PERTUMBUHAN DAN KANDUNGAN KARAGINAN RUMPUT LAUT Kappaphycus striatum DENGAN MENGGUNAKAN MEDIA BUDIDAYA YANG BERBEDA DI PERAIRAN DESA OENAEK, NUSA TENGGARA TIMUR - Windya Ynryani Boimau; Ridwan Tobuku; Nicodemus Dahoklory (Jurnal Aquatik, 2026)
The aim of this study was to evaluate the effect of different culture media on the growth and carrageenan content of the seaweed Kappaphycus striatum. The study was conducted over 45 days in the waters off Oenaek Village, Kupang Regency, using three types of cultivation media: UV-treated plastic (Treatment A), mesh bags (Treatment B) and the conventional or long-line method (Treatment C), each with three replicates. The parameters observed included absolute weight growth, specific growth rate, and carrageenan content. The results showed that the conventional method (Treatment C) yielded the best results compared to the other treatments, with an average absolute weight growth of 296.99 g and a specific growth rate of 4.30% per day. The highest carrageenan content was also found in Treatment C, at 111 per cent. Statistical analysis using ANOVA showed no statistically significant effect on absolute growth and SGR (p > 0.05); however, from a biological perspective, the conventional medium yielded the most optimal results. These findings indicate that the conventional cultivation method (long line) is more effective in enhancing the productivity and quality of K. striatum seaweed. Keywords: Kappaphycus striatum, carrageenan, cultivation medium, long line, growth